Equivalent Surface Impedance of Slot Impedance Load Based on Aperture in Parallel-Plate Dielectric-Coated Waveguide Wall as Part of Infinite Array - V. G. Koshkidko; O. V. Alpatova (Известия высших учебных заведений России: Радиоэлектроника, 2017)
The problem of infinite array of slot impedance loads with dielectric coating excitation by plane wave is considered with the purpose of determining the equivalent surface impedance. Each array element consists of three areas and The area is the half space above the delimiter boundary. In this area the primary field is excited by the plane wave. The area does not contain any excitation sources and consists of dielectric layer of t thickness located between the planes and The area does not contain any excitation sources either and is bounded by parallel-plate waveguide walls with the distance b between them. The area is connected with the area by one or several slots in the top wall of the parallel-plate waveguide placed on the boundary of volumes and . A plane conductor is placed in the aperture of each slot. Excitation source characteristics and construction parameters do not depend on z coordinate (2D-problem). The problem is solved by the integral equation method and is calculated by the Krylov-Bogolyubov method so that the integral equation is reduced to the system of linear algebraic equations. To overcome mathematical difficulties dealing with logarithmic singularity in the kernel of the integral equation Kummer transformation is used. This allows not only improving the series convergence but also getting the logarithmic singularity in explicit form and integrating it analytically. Numerical results are given as equivalent surface impedance dependencies on the construction geometrical dimensions for fixed values of the averaging interval, the plane wave incidence angle and the thickness of the dielectric layer. It is shown that equivalent surface impedance can be varied by changing the slot width and the plane conductor width. A comparative analysis of the obtained dependencies possessing impedance load characteristics with no dielectric coating is carried out.